2017
DOI: 10.4172/2155-6113.1000652
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity, Stigma and Adherence to Antiretroviral Therapy (ART) among People Living with HIV/AIDS in Guangxi, China

Abstract: This study examines the impact of ethnicity and multiple types of HIV-related stigma on adherence to antiretroviral therapy (ART) among 2,146 people living with HIV/AIDS (PLWHA) in Guangxi, China who had initiated ART. The results of multiple binary logistic regressions indicate that those who had experienced enacted stigma tended to report lower adherence, while better adherence was associated with older age, being women and having a job. Ethnicity had a moderator effect on the association between internalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
8
1
Order By: Relevance
“…Overall, 53.76% of pregnant women experienced HIVrelated stigmatization. The proportion was lower, comparative to 79.1% of internalized stigmatization in the United States, 77.8% of overt stigmatization in women from Chile, and 62.2% of anticipatory stigmatization in PLWH receiving ART in the Oromia region, Ethiopia (5,6,25); however, our number was found to be greater than the 29.0% of enacted stigmatization in PLWH in South Africa, and 25.2% in depressed pregnant women living with HIV in Kenya, and less than the 10% enacted stigmatization in participants at HIV clinics in Guangxi China (7,13,21). Difference in the HIV-related stigma was partially due to variations in social background and culture, participants' characteristics and perspectives toward HIV.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Overall, 53.76% of pregnant women experienced HIVrelated stigmatization. The proportion was lower, comparative to 79.1% of internalized stigmatization in the United States, 77.8% of overt stigmatization in women from Chile, and 62.2% of anticipatory stigmatization in PLWH receiving ART in the Oromia region, Ethiopia (5,6,25); however, our number was found to be greater than the 29.0% of enacted stigmatization in PLWH in South Africa, and 25.2% in depressed pregnant women living with HIV in Kenya, and less than the 10% enacted stigmatization in participants at HIV clinics in Guangxi China (7,13,21). Difference in the HIV-related stigma was partially due to variations in social background and culture, participants' characteristics and perspectives toward HIV.…”
Section: Discussioncontrasting
confidence: 66%
“…China is a country with an immense population and contains tremendous ethnic diversity, and the association between stigmatization and social support among pregnant women with HIV or syphilis remains poorly understood. Previous studies showed that HIV-positive pregnant women experienced more psychological distress and stigmatization than men, and HIVrelated stigmatization was negatively associated with social support (9,(20)(21)(22). A majority of these studies in China focused on women living in HIV epidemic areas.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study by Aye et al revealed that patients who disclosed their HIV status to others were less likely to comply with ART than those who did not disclose their status [23]. Other studies indicated that although disclosure can lead to a support from a social network, there is a high level of perceived stigma with initial disclosure to a trusted family member rather than a partner [37]. These differences suggest that the association between adherence, social support, disclosure, and stigma is complicated and dynamic.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of supportive environment, the vulnerability of personal privacy information to disclosure in the implementation of HIV health services, as well as AIDS-related discrimination and stigma pose a threat to the quality of health services, and have a serious impact on patients' mental health and the quality of health services. Research by Rames [39] and Yuchen Mao [40] suggests that social stigma is common, and this stigma and social stress can lead to depression, reduced quality of life and negative treatment outcomes. We suggested that regulatory agencies should work to reduce stigma effects.…”
Section: Discussionmentioning
confidence: 99%